When 3 Rs meet a forth R: Replacement, reduction and refinement of animals in research on reproduction. (April 2019) - Arck, Petra Clara
Highlights: Proposition of measures for the implementations of the 3R principles in research on reproduction. Discussion of insights arising from animal models and their translational relevance. Suggestions for future directives in animal research in reproductive immunology. Abstract: Research endeavors aiming to understand the maternal immune adaptation to pregnancy significantly rely on the use of animal models, such as mice and rats. These models have provided important insights into the pathophysiology of a number of pregnancy disorders in humans. However, the use of animal models in scientific research is a vividly debated and emotive topic. The 3R principles – replacement, reduction and refinement of research animals – have been propagated a few decades ago. The present review advocates a forward-thinking consciousness to address the 3R principles in research projects in the field of reproductive biology and immunology. Specific measures and alternative methods are being proposed to replace research animals by using e.g. tissue engineering approaches, biobank-derived tissue, 'placenta-on-a-chip' devices or in silico methods. The latter may involve data queries from repositories now available to provide single cell sequencing information on reproductive tissues. Reduction of research animals by gestational imaging and a wealth of suggestions for refinement are proposed. Taken together, the measures and guidelines introduced in this review are expected to spark a reconsideration of experimental designs in the area of reproductive biology and immunology in order to implement 3R principle where applicable.